Pengembangan E-Modul Ajar Fisika Bermuatan CHATGPT Pada Materi Gerak Lurus - Fajrin, Moh; Pasaribu, Marungkil; Paramita, Ielda; Santoso, Rudi (UIN Alauddin Makassar, 2025)
This study aims to determine the process of developing a teaching e-module, its feasibility, and student responses to the use of a teaching e-module containing ChatGPT as a teaching material. The type of research used is Research and Development (R&D) with the ADDIE model, which includes five stages: (1) analysis, (2) design, (3) development, (4) implementation, and (5) evaluation. This study used a questionnaire as the research instrument. The resulting product is an interactive teaching e-module that integrates ChatGPT in learning on straight-lead motion. Validation results by material experts showed an average score of 3.85 (categorized as